Storytelling in dementia: Embodiment as a resource. (May 2013) - Hydén, Lars-Christer
In narrative research about persons with dementia, much research focuses on individual storytellers and their stories often stressing the discursive or textual aspects of stories. As persons with Alzheimer's disease generally have difficulties in telling stories according to often implicit narrative norms, they may appear to be less competent and agentive than what is actually the case. In the article, I argue for a change of focus from the textual aspects of narratives and the story as a product, to a focus on performative aspects and the embodied aspects of storytelling. A focus on the storytelling activity implies a change from the individual storyteller to the interaction with other participants in the storytelling situation. Drawing on two particular cases of storytelling, I stress the collaborative and embodied aspects of storytelling and argue that embodiment is less an individual expressive phenomenon than it is an interactive resource.